2023
DOI: 10.3390/ma16051794
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Compressive Strength and Microscopic Properties of Portland Cement Taking Attapulgite and Montmorillonite Clay as an Additive

Abstract: The effects of attapulgite and montmorillonite calcinated at 750 °C for 2 h as supplementary cementing materials (SCMs) on the working properties, mechanical strength, phase composition, morphology, hydration and heat release of ordinary Portland cement (OPC) were studied. The results show that pozzolanic activity increased with time after calcination, and with the increase in content of calcined attapulgite and calcined montmorillonite, the fluidity of cement paste exhibited a downward trend. Meanwhile, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It is characterized by an open-channel structure that gives rise to elongated, needle-shaped crystals [71]. Attapulgite is an effective supplementary cementitious material [69], [70], [71]. The introduction of a small quantity of attapulgite substantially impacted the formation of the cement paste's structural network, leading to a more flocculated internal arrangement.…”
Section: X-ray Diffraction Analysis Of Fly Ash and Ggbsmentioning
confidence: 99%
“…It is characterized by an open-channel structure that gives rise to elongated, needle-shaped crystals [71]. Attapulgite is an effective supplementary cementitious material [69], [70], [71]. The introduction of a small quantity of attapulgite substantially impacted the formation of the cement paste's structural network, leading to a more flocculated internal arrangement.…”
Section: X-ray Diffraction Analysis Of Fly Ash and Ggbsmentioning
confidence: 99%
“…Due to its special structure, palygorskite is commonly used in the field of adsorption curing, such as curing heavy metal elements in sewage and soil [19,20]. Aconite is abundant and cheap, it can be modified by calcination and other methods and promote the early hydration reaction [21,22], improving the effect of the early mechanical properties of cementitious materials. palygorskite is mostly used in the construction field [23][24][25][26], but little research has been reported in the filling field.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that its mechanical strengths were improved by consuming a large amount of Ca(OH) 2 and forming more compact hydration products. Furthermore, Yan et al [ 8 ] used natural minerals (calcined attapulgite and montmorillonite) as additives to improve the early and late compressive strength of cement paste.…”
mentioning
confidence: 99%